1985
DOI: 10.1182/blood.v66.1.59.59
|View full text |Cite
|
Sign up to set email alerts
|

Serial studies of protein C and its plasma inhibitor in patients with disseminated intravascular coagulation

Abstract: This study was undertaken to determine the levels of protein C antigen and activity and protein C inhibitor in sequential plasma samples of disseminated intravascular coagulation (DIC) patients. Our normal range for both protein C antigen and activity is 70 to 130 U/dL, and protein C inhibitor is 65 to 135 U/dL. A decreased level of protein C activity was found in 96% of the plasma samples from individuals with DIC; the protein C antigen was decreased in 73%. The inhibitor of protein C was decreased in all sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(28 citation statements)
references
References 15 publications
1
27
0
Order By: Relevance
“…We observed in septic patients that an activation of the coagulation system is always accompanied by indicators of an activated fibrinolytic system, which confirms several related reports in the literature: firstly, most authors who give a laboratory definition of disseminated intravascular coagulation include the increase of fibrin/fibrinogen degradation products into their definition (Corrigan & Jordan, 1970;Corrigan, 1977;Mant & King, 1979;Kreger et al 1980;Neame et al, 1980;Gallimore et al, 1980;Tran et al, 1981;Feinstein, 1982: Kobayashi et al, 1983Laemmle etal, 1984;Hellgren et al 1984;Egberg & Hellgren, 1985;Marlar et al, 1985;Wilde et al, 1989); secondly, Nossel et a1 (1979) showed that an acute activation of coagulation in vivo by intrauterine administration of hypertonic saline induced a pronounced activation of plasminogen with only a very short time delay: thirdly, after operations which of course induce an activation of coagulation, a pronounced increase in the cross-linked fibrin degradation product D-dimer was found, which was not due to an evolving thrombosis (abdominal surgery: Hauch et al, 1988: hip surgery : Wilson et al, 1988).…”
Section: Resultssupporting
confidence: 79%
“…We observed in septic patients that an activation of the coagulation system is always accompanied by indicators of an activated fibrinolytic system, which confirms several related reports in the literature: firstly, most authors who give a laboratory definition of disseminated intravascular coagulation include the increase of fibrin/fibrinogen degradation products into their definition (Corrigan & Jordan, 1970;Corrigan, 1977;Mant & King, 1979;Kreger et al 1980;Neame et al, 1980;Gallimore et al, 1980;Tran et al, 1981;Feinstein, 1982: Kobayashi et al, 1983Laemmle etal, 1984;Hellgren et al 1984;Egberg & Hellgren, 1985;Marlar et al, 1985;Wilde et al, 1989); secondly, Nossel et a1 (1979) showed that an acute activation of coagulation in vivo by intrauterine administration of hypertonic saline induced a pronounced activation of plasminogen with only a very short time delay: thirdly, after operations which of course induce an activation of coagulation, a pronounced increase in the cross-linked fibrin degradation product D-dimer was found, which was not due to an evolving thrombosis (abdominal surgery: Hauch et al, 1988: hip surgery : Wilson et al, 1988).…”
Section: Resultssupporting
confidence: 79%
“…In the coagulation system, APC reduces thrombin and therefore fibrin formation by inactivating the clotting factors Va and VIIIa. Serial studies of PC and its' plasma inhibitor in patients with DIC provide compelling evidence for a major modulatory role for PC in DIC (Marlar et al, 1985). The possibility exists therefore that, in the patients described in this report, PCC-induced coagulation activation was reduced or suppressed by the simultaneous correction of the acquired PC deficiency.…”
Section: Discussionmentioning
confidence: 62%
“…The level of PCI in plasma is decreased in patients with intravascular hypercoagulation such as deep vein thrombosis, pulmonary embolism and disseminated intravascular coagulation [54,55]. Although the plasma PCI level is only slightly decreased in patients with systemic lupus erythematosus [56], diabetes mellitus [57], myocardial infarction [58,59] or relatively mild intravascular coagulation such as pulmonary embolism and deep venous thrombosis [60] and aortic aneurysms [61], significant increases in the level of the APC-PCI complex are observed in these patients.…”
Section: Regulation Of Thrombosis and Fibrinolysis By Pcimentioning
confidence: 99%